Research of the new myelostimulators among of herbal preparations, derived from plants growing in arid zone of Kazakhstan (Experimental biology, 2015)
Research of the new myelostimulators among of herbal preparations, derived from plants growing in arid zone of Kazakhstan under the following Identifier codes: Halostachys caspia (aqueous extract) – IES.SPP.401R, Holostachys caspia (50% water – ethanol extract) – IES.SPP.401R.SE, Sueda microphylla (aqueous extract) – SIE.SM.401R , Sueda microphilla (50% water – ethanol extract) – SIE.SM.401R.SE, Climacoptera obbtusifolia (70% water – ethanol extract) – G.COEX, Climacoptera lanata (70% water – ethanol extract) -G.CLEX, Climacoptera subcrassa (aqueous extract) -A.SKF, Climacoptera subcrassa (50% water – ethanol extract) -A.CSEX. The highest myelostilating results were from compound SIE.SM.401R.SE.
Keywords: myelostimulator; herbal preparations; leucopoies; lymphopoies; myelopoies